KREATIVITAS BARISTA DALAM PERACIKAN KOPI DI NORU COFFEE BUKITTINGGI - Muhammad Ridho Rizky; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Noru Coffee Bukittinggi is one of the cafes with quite a lot of guest visits, this is because the coffee menu that is served varies which is prepared by trained baristas from the cafe. The importance of the creativity of a barista in creating a cup of espresso and beautiful painting on coffee foam greatly affects the quality of the coffee. This research was conducted to see the creativity of a barista in preparing a cup of coffee. This study uses qualitative methods, while the data analysis techniques in this study use observation, in-depth interviews and documentation. The key information in this research is the 7 employees of Noru Coffee. The purpose of this study is to analyze in depth the creativity of Noru Coffee's baristas who have succeeded in creating delicious coffee flavors so that Noru Coffee is visited by guests from all walks of life. Keywords: Creativity, Barista and Coffee.